Hell's highway KM 31 - Rovzar, Billy; Rovzar, Fernando; Castaneda, Rigoberto; Lemon Films; Santo Domingo Films ([Mexico] : The Films, 2008)
After a mysterious accident on kilometer 31, Agata falls into a coma. Her twin sister Catalina telepathically feels her pain and hears her whispering for help. Together with her boyfriend Nuno and Agata's mate Omar, they return to kilometer 31 of the road. Soon, they discover that the place is surrounded by supernatural accidents caused by the ghost of a mother who lost her son many years ago. Catalina then finds out that Agata's spirit is trapped between the world of the living and the dead
Titles from title screen
Based on true story
Cast: Iliana Fox, Adria Collado, Raul Mendez, Julian Alvarez, Carlos Aragon, Everardo Arzate
DVD Format
Dolby digital
In Spanish with optional Chinese Traditional, Chinese Simplified, English or Malay subtitles
Keywords: Ghosts -- Drama; Suspense in motion pictures; Horror films